(untitled) (Nativa, 2025)
The objective was to establish and evaluate the similarity of the Kenworthy and DRIS norms for the Prata banana in soils with improved fertility. The data used were leaf nutrient contents and yields of 180 plots from an experiment with two cultivars (Prata-Anã and BRS Platina), five doses of K2O (0; 200; 400; 600 and 800 kg ha-1) supplied with sources for organic management and six evaluation times (210; 390; 570; 750; 930 and 1,110 days after planting), in a randomized block design in the factorial scheme, with three replicates. The database was separated from the average yield, 36.42 t ha-1 cycle-1 for ‘Prata-Anã’ and 38.4 t ha-1 cycle-1 for ‘BRS Platina’, into low-yielding population (LYP) and high-yielding population (HYP). Mean, standard deviation, coefficient of variation, variance and variance ratio (HYP/LYP) of nutrients and their bivariate ratios, direct (A/B) and inverse (B/A), were calculated. ‘Prata-Anã’ and ‘BRS Platina’ in HYP differed in terms of the means and variances for Kenworthy by 33.00%, for the DRIS, the means differed in 71.21% and variances in 43.18% of the cases. The Kenworthy and DRIS norms established support the nutritional diagnosis of ‘Prata-Anã’ and ‘BRS Platina’ banana plants grown in soils with improved fertility. Keywords: Musa spp.; plant nutrition; leaf analysis; equilibrium; nutritional balance. Normas Kenworthy e DRIS para bananeiras ‘Prata-Anã’ e ‘BRS Platina’ em solos de fertilidade construída RESUMO: Objetivou-se estabelecer e avaliar a similaridade das normas Kenworthy e DRIS para bananeiras tipo Prata em solos com fertilidade construída. Utilizaram-se teores de nutrientes das folhas e produtividades de 180 parcelas, de experimento com duas cultivares (Prata-Anã e BRS Platina), cinco doses de K2O (0; 200; 400; 600 e 800 kg ha-1) supridas com fontes para manejo orgânico e seis épocas de avaliação (210; 390; 570; 750; 930 e 1.110 dias após plantio), em delineamento em blocos casualizados em esquema fatorial, com três repetições. Separou-se o banco de dados, a partir da produtividade média (36,42 t ha-1 ciclo-1 para a ‘Prata-Anã’ e de 38,4 t ha-1 ciclo-1 para a ‘BRS Platina’) em população de baixa (PBP) e alta produtividade (PAP). Calcularam-se as médias, desvio-padrão, coeficientes de variação, variâncias e razão das variâncias (PBP/PAP) dos nutrientes e de suas relações bivariadas, direta (A/B) e inversa (B/A). ‘Prata-Anã’ e ‘BRS Platina’ na PAP diferiram quanto às médias e variâncias para Kenworthy em 33,0%, já para o DRIS, médias diferiram em 71,21 % e variâncias em 43,18% dos casos. As normas Kenworthy e DRIS estabelecidas subsidiam o diagnóstico nutricional das bananeiras ‘Prata-Anã’ e ‘BRS Platina’ cultivadas em solos com fertilidade construída. Palavras-chave: Musa spp.; nutrição de plantas; análise foliar; equilíbrio; balanço nutricional.